The Difference in the Source of Bee Bread (Citrus, Anise) in Its Chemical Composition - Aldarf , Rouba Jihad; Sultaneh , Ali (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Beebread is a hive product derived from the collection of pollen by bees. To produce beebread, bees enrich the gathered pollen with honey and digestive enzymes, storing the mixture within the combs. The transformation of bee pollen into beebread occurs through an anaerobic fermentation process facilitated by the bees. Effective beehive management is crucial to encourage the accumulation of beebread, with the intention of marketing it for human consumption. This is due to its recognition as a valuable nutritional supplement, attributed to its rich array of nutrients. The nutritional value of beebread, including protein, amino acids, fatty acids, carbohydrates, and polyphenols, is contingent upon the plant source of the bee pollen, emphasizing the significance of proper hive management for optimizing its quality. The nutritional and functional composition of beebread lead this research, work was done to collect bee bread from two different geographical regions, namely the coastal region (Lattakia), which was the predominant citrus at the time of collection and the interior region (the countryside of Hama), which was aniseed prevalent at the time of collection. The results of the research showed the difference in the chemical composition of bee bread collected from the two mentioned areas. The protein content of bee bread samples from the interior region increased, which amounted to 20%, with a very high significance compared to bee bread from the coastal region, which amounted to 15.6%. The content of sinters also increased with a very high significance, which amounted to 7.92% and 2.02% in the interior and coastal regions, respectively. As for the ash, it was 2% and 1.3% in the interior and coastal regions, respectively. As for the humidity of the samples of the interior region, it was lower than that of the coastal region, which amounted to 8.68%, while 13.5% in the coastal region. The results also showed the difference in the content of the studied bee bread samples in fructose, where the content of the samples of the interior region amounted to 23.07%, while the content of the samples of the coastal region amounted to 18.10%, while the content of glucose sugar reached 15.74% and 14.82% in both the interior and coastal regions, respectively. This confirms the difference in the chemical composition of bee bread according to the plant type from which bee pollen was collected.